A Rapid and Reversible pH Control Process for the Formation and Dissociation of Lignin Nanoparticles. Issue 8 (25th March 2022) - Xu, Jiayun; Zhou, Hao; Zheng, Yong; Li, Chenyu; Dai, Lin; Xu, Chunlin; Si, Chuanling
Abstract: As a new and green type of nanomaterials, lignin nanoparticles (LNPs) have been considered as high‐value renewable materials for application in many fields. However, the industrialization of LNPs faces many challenges, such as high manufacturing costs and small‐scale production. Here, a simple but rapid and reversible approach for the fabrication of LNPs was provided via switching pH environments. The LNPs were regularly shaped in the acetonitrile/water system, and their size appeared to be very homogeneous. The alternation of forming and dissolving of LNPs could be repeated many times simply by alternately adding acid and alkaline solutions. There was little difference in the molecular structures between the original and regenerated LNPs. In addition, the consumption of solvents for LNPs production was only 200 mL g −1, reduced by more than 10 times compared with conventional solvent exchange methods. The concentration of LNPs in the solution also improved to 5.0 g L −1 . This study not only provides a new, simple, and effective strategy for the fabrication of LNPs but also paves the way towards their real green production and application. Abstract : Flip the switch : A simple, rapid, and reversible approach for the fabrication of lignin nanoparticles can be repeated many times simply by alternately adding acid and alkaline solutions without destroying the molecular structures of lignin. The consumption of solvents in the lignin nanoparticles production is only 200 mL g −1, reduced by more than 10 times compared with conventional solvent exchange methods.